2007
DOI: 10.1152/ajpcell.00293.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role for IκBα, but not c-Rel, in skeletal muscle atrophy

Abstract: Skeletal muscle atrophy is associated with a marked and sustained activation of nuclear factor-kappaB (NF-kappaB) activity. Previous work showed that p50 is one of the NF-kappaB family members required for this activation and for muscle atrophy. In this work, we tested whether another NF-kappaB family member, c-Rel, is required for atrophy. Because endogenous inhibitory factor kappaBalpha (IkappaBalpha) was activated (i.e., decreased) at 3 and 7 days of muscle disuse (i.e., hindlimb unloading), we also tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
145
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(159 citation statements)
references
References 60 publications
(73 reference statements)
13
145
0
1
Order By: Relevance
“…These data correlate well with previously published data on decreased I κ B α content in mice during 3‐ and 7‐day unloading (Judge et al. 2007). We showed that pharmacological inhibition of IKKβ activity using IMD‐0354 during unloading blocked I κ B α degradation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These data correlate well with previously published data on decreased I κ B α content in mice during 3‐ and 7‐day unloading (Judge et al. 2007). We showed that pharmacological inhibition of IKKβ activity using IMD‐0354 during unloading blocked I κ B α degradation.…”
Section: Discussionmentioning
confidence: 99%
“…A similar decrease in the I κ B α level of expression was reported previously after 3 and 7 days of unloading in the rat model (Judge et al. 2007). Mice with muscle‐specific transgenic expression of activated IKK β have profound muscle wasting due to the activation of NF‐ κ B/MuRF (Cai et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations